2016
DOI: 10.1007/s00228-016-2153-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cytochrome P450 (CYP3A4 and CYP2C19) inhibition and induction on the exposure of selumetinib, a MEK1/2 inhibitor, in healthy subjects: results from two clinical trials

Abstract: PurposeTwo phase I, open-label trials in healthy subjects assessed whether co-administration with CYP3A4/CYP2C19 inhibitors, itraconazole/fluconazole (study A), or CYP3A4 inducer, rifampicin (study B), affects the exposure, safety/tolerability and pharmacokinetics of selumetinib and its metabolite N-desmethyl selumetinib.MethodsIn study A (n = 26), subjects received a single dose of selumetinib 25 mg and, after 4 days of washout, were randomized to treatment 1 (itraconazole 200 mg twice daily on days 1–11) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(56 citation statements)
references
References 13 publications
3
48
0
Order By: Relevance
“…Additional safety and tolerability data for the Western studies are reported in detail elsewhere and include references [2022]. …”
Section: Methodsmentioning
confidence: 99%
“…Additional safety and tolerability data for the Western studies are reported in detail elsewhere and include references [2022]. …”
Section: Methodsmentioning
confidence: 99%
“…N‐desmethyl selumetinib is metabolized through the same routes as the parent drug. In studies, selumetinib, N‐desmethyl selumetinib, and glucuronide conjugates of both were the major components identified in human plasma, and the amide metabolite was also detected in human plasma . N‐desmethyl selumetinib is an active metabolite, and shows a 3‐ to 5‐fold greater potency for MEK1 inhibition in vitro than the parent compound.…”
mentioning
confidence: 99%
“…Selumetinib has a short half‐life (5‐7 hours), and its pharmacokinetic (PK) profile is approximately dose‐proportional from 25 mg to 150 mg in patients with advanced cancer . Cytochrome P450 (CYP) 1A2, 2C19, 3A4, and 3A5 are mainly responsible for the metabolism of selumetinib, with CYP1A2 being the enzyme primarily responsible for the formation of the N‐desmethyl metabolite . N‐desmethyl selumetinib is metabolized through the same routes as the parent drug.…”
mentioning
confidence: 99%
See 2 more Smart Citations